Earliest Christianity within the boundaries of Judaism : essays in honor of Bruce Chilton - Chilton, Bruce.; Avery-Peck, Alan J. 1953- (The Brill Reference Library of Judaism, 2016)
Twenty-two essays, written by top scholars in the fields of early Christianity and Judaism, focus on methodological issues, earliest Christianity in its Judaic setting, Gospel studies, and history and meaning in later Christianity. These essays honor Bruce Chilton, recognizing his seminal contribution to the study of earliest Christianity in its Judaic setting. Chilton's scholarship has established innovative approaches to reconstructing the life of Jesus, a Jew whose religious ideology developed and therefore must be understood within the Judaism of the first centuries. Following upon Chilton's approaches and insights, the essays collected here illustrate the centrality of the literatures of early Judaism to the critical exegesis of the New Testament and other writings of early Christianity.